2017
DOI: 10.1002/cphc.201701096
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Role of Long‐Range Forces in the Stereodynamics of Ion–Molecule Reactions: The He++Methyl Formate Case From Guided‐Ion‐Beam Experiments

Abstract: Long‐range intermolecular forces play a crucial role in controlling the outcome of ion–molecule chemical reactions, such as those determining the disappearance of organic or inorganic “complex” molecules recently detected in various regions of the interstellar medium due to collisions with abundant interstellar atomic ions (e.g. H+ and He+). Theoretical treatments, for example, based on simple capture models, are nowadays often adopted to evaluate the collision‐energy dependence of reactive cross sections and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 82 publications
0
24
1
Order By: Relevance
“…The difference between our measured BRs (Cernuto et al 2017(Cernuto et al , 2018 and those reported in the KIDA and UDfA databases is striking, as shown in the Tables 1 and 2. The uncertainties on our experimental BRs derive from error propagation in the cross section measurements.…”
Section: Branching Ratioscontrasting
confidence: 59%
See 4 more Smart Citations
“…The difference between our measured BRs (Cernuto et al 2017(Cernuto et al , 2018 and those reported in the KIDA and UDfA databases is striking, as shown in the Tables 1 and 2. The uncertainties on our experimental BRs derive from error propagation in the cross section measurements.…”
Section: Branching Ratioscontrasting
confidence: 59%
“…From the discussion in §3, it is clear that the new rate coefficients, based on the experimental results by Cernuto et al (2017Cernuto et al ( , 2018, differ from the those reported in both KIDA and UDfA databases in terms of their absolute values, their temperature dependence (which is positive rather than negative) as well as in the product BRs. An interpolation of the new rate coefficients (and extrapolated values at very low temperatures) gives the following parameters for the global destruction rate coefficients of DME and MF through reaction with He + : α = 1.4 × 10 −9 , β=+0.295, γ=0.00 for DME and α = 1.4 × 10 −9 , β=+0.241, γ=0.00 for MF.…”
Section: New Values To Adopt In the Astrochemical Networkmentioning
confidence: 75%
See 3 more Smart Citations